HOX13-dependent chromatin accessibility underlies the transition towards the digit development program - Ines Desanlis (Nature Portfolio, 2020)
Pioneer factors direct cell fate through switching inaccessible chromatin to an accessible state at specific target enhancers. Here the authors show that HOX13 transcription factors have a pioneer activity which is required for the proper implementation of the distal limb developmental program.